1994
DOI: 10.1159/000187986
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidemia after Renal Transplantation: Treatment with Gemfibrozil

Abstract: Thirty-eight renal allograft recipients who had persistent hyperlipidemia and stable renal function 27.8 ± 18.2 months after renal transplantation were treated with gemfibrozil. Gemfibrozil therapy resulted in a decrease in the levels of total cholesterol (TC; 297.6 ± 41.0 mg/dl to 249.2 ± 43.7 mg/dl, -16.3%; p < 0.0001), triglyceride (TG; 231.9 ± 116.8 to 125.7 ± 58.4 mg/dl, -45.8%, p < 0.0005), and LDL-cholesterol (LDL-C; 203.8 ± 37.4 to 174.5 ± 42.5 mg/dl, -14.4%; p = 0.001), which were sustained for 29.1 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…Significant reductions in plasma lipid levels were also achieved in patients without marked hyperlipidemia. The relative decreases in the levels of total cholesterol, L D L cholesterol and triglycerides were comparable to reductions of these lipid constituents re ported in previous studies of patients with chronic renal failure [9] or renal transplant patients [6] treated with gemfibrozil.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Significant reductions in plasma lipid levels were also achieved in patients without marked hyperlipidemia. The relative decreases in the levels of total cholesterol, L D L cholesterol and triglycerides were comparable to reductions of these lipid constituents re ported in previous studies of patients with chronic renal failure [9] or renal transplant patients [6] treated with gemfibrozil.…”
Section: Discussionsupporting
confidence: 82%
“…The fibrates have been shown to increase the lipoprotein lipase activity, to lower elevated serum triglycerides, to reduce the LD L cholesterol and to increase the H D L cho lesterol levels in non-renal patients [25]. Fibric acid deriv atives have also been shown to reduce plasma lipids, i.e., serum triglycerides, total cholesterol and LD L cholesterol in nephrotic patients [26,27], in patients with renal insuf ficiency [24,28,29] and in stable renal transplant patients [6,9], However, none of these studies investigated the effects of a fibrate derivative on apolipoproteins or indi vidual lipoprotein particles in predialytic renal patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LDL-C, and HDL-C levels. In a retrospective study conducted by Chan et al [7], it was found that 300-600 mg GF/ day caused important decreases in TG, TC and LDL-C but did not induce an important increase in HDL-C. In our prospective study, significant differences were observed in all 4 parameters, probably due to the high er dose (1,200 nig/day) used without any sig nificant side effects.…”
supporting
confidence: 40%
“…Bile acid sequestrants and nicotinic acid generally are not considered first‐line cholesterol‐lowering therapy in transplant recipients because of side‐effects and drug interactions, and gemfibrozil and probucol are not preferred because their lipid‐lowering effects are modest (31,35,73). Some investigators have reported significant reductions in total cholesterol, LDL cholesterol, and triglyceride levels in renal‐transplant recipients receiving gemfibrozil therapy (83). Fenofibrate lowered total cholesterol, LDL cholesterol, and triglyceride levels by about 20% in one study of heart‐transplant recipients, but was associated with a 67% withdrawal rate because of side‐effects (71).…”
Section: Dyslipidemiamentioning
confidence: 99%